Exam preparation course in obstetrics and gynecology for the German Medical State Examination: proof of concept and implications for the recruitment of future residents - Riedel, Fabian; Fremd, Carlo; Smetanay, Katharina; Marshall, Anne; Heil, Jörg; Schütz, Florian; Sohn, Christof; Hennigs, André (Archives of gynecology and obstetrics, 2016)
ObjectivesToday´s written part of the medical state examination requires students to retrieve a comprehensive amount of knowledge in a limited period of time. Therefore, the main study objectives were to implement and to evaluate a two-day exam preparation course for the German Medical State Examination in obstetrics and gynecology. The project evaluation focused on acceptability, satisfaction and the gain of knowledge for the participants of such a face-to-face course.Study designThe two-day intensive training for senior medical students offered a review of the entire exam-relevant content in the field of obstetrics and gynecology in combination with interactive discussions along selected exam questions. Skill gains were assessed using pre- and post-course multiple choice tests. In addition, a qualitative questionnaire assessed attitudes and satisfaction of course participants.ResultsA total of 101 fifth year senior medical students from Heidelberg University Medical School participated in the two pilot courses (summer 2014 and winter 2015). Pre- and post-course tests showed a significant skill-gain from 14.9 to 18.0 points [of a maximum of 20; pre-post difference 95 % CI (2.21; 3.98), t test: p < 0.001]. Furthermore, the qualitative results showed high satisfaction with the course, with an average Likert scale grading of 5.63 (2014) and 5.44 (2015) on a scale from 1 (“extraordinary bad”) to 6 (“extraordinary good”).ConclusionsThis study shows that a two-day intensive course in obstetrics and gynecology is feasible, effective and highly appreciated by senior medical students preparing for the Second German Medical State Examination. It further suggests surplus value for academic clinical departments to recruit future residents. Methods and tools presented in this paper are intended to inspire and guide clinical colleagues in implementing the format at their respective universities.
Gesehen am 06.12.2017